Dynamic evaluation of postoperative survival in intrahepatic cholangiocarcinoma patients who did not undergo lymphadenectomy: a multicenter study. (1st February 2023) - Huang, Tingfeng; Kong, Jie; Liu, Hongzhi; Lin, Zhipeng; Lin, Qizhu; Lou, Jianying; Zheng, Shuguo; Bi, Xinyu; Wang, Jianming; Guo, Wei; Li, Fuyu; Wang, Jian; et al.
Abstract: Background: The prognosis of Intrahepatic cholangiocarcinoma (ICC) patients who did not undergo lymphadenectomy is difficult to assess. This study aims to have a dynamic evaluation on the postoperative survival of ICC patients by calculating conditional survival. Methods: Relevant data were from patients treated in 12 large-scale hospitals from December 2011 to December 2017. The influence of relevant clinical baseline data on the prognosis of ICC patients was analyzed by Cox regression. Conditional survival (CS) is a method that may predict the prognostic probability dynamically. For a patient with x years of survival, the 1-year CS (CS1) may be calculated as CS1= OS( x  + 1)/OS(x). Result: A total of 361 patients who met the criteria were included in the study. Conditional survival (CS) means that the patients' prognosis varies with survival time, meanwhile, relevant factors affecting the prognosis have a time-varying effect. The probability of survival assessed by CS1 increased year by year and the 1, 2, 3-year survival improved from 68.4% to 87.8%, while the postoperative actuarial OS decreased from 69.4% at 1 years to 36.9% at 3 years. Conclusions: In terms of CS, the estimated survival for ICC varies with the increase of survival time after excision. Patients who live longer were likely to live longer. At the same time, with the passage of time, the role of the original adverse factors of the tumor would gradually decrease. Conditional survival allows a more accurate assessment of ICC patients who did not undergo lymphadenectomy.